A novel GH3-β-glucosidase from soda lake metagenomic libraries with desirable properties for biomass degradation - Oliyad Jeilu; Erik Alexandersson; Eva Johansson; Addis Simachew; Amare Gessesse (Scientific Reports, 2024)
Abstract Beta-glucosidases catalyze the hydrolysis of the glycosidic bonds of cellobiose, producing glucose, which is a rate-limiting step in cellulose biomass degradation. In industrial processes, β-glucosidases that are tolerant to glucose and stable under harsh industrial reaction conditions are required for efficient cellulose hydrolysis. In this study, we report the molecular cloning, Escherichia coli expression, and functional characterization of a β-glucosidase from the gene, CelGH3_f17, identified from metagenomics libraries of an Ethiopian soda lake. The CelGH3_f17 gene sequence contains a glycoside hydrolase family 3 catalytic domain (GH3). The heterologous expressed and purified enzyme exhibited optimal activity at 50 °C and pH 8.5. In addition, supplementation of 1 M salt and 300 mM glucose enhanced the β-glucosidase activity. Most of the metal ions and organic solvents tested did not affect the β-glucosidase activity. However, Cu2+ and Mn2+ ions, Mercaptoethanol and Triton X-100 reduce the activity of the enzyme. The studied β-glucosidase enzyme has multiple industrially desirable properties including thermostability, and alkaline, salt, and glucose tolerance.